2021
DOI: 10.1038/s41467-021-26476-5
|View full text |Cite
|
Sign up to set email alerts
|

Atomic scale crystal field mapping of polar vortices in oxide superlattices

Abstract: Polar vortices in oxide superlattices exhibit complex polarization topologies. Using a combination of electron energy loss near-edge structure analysis, crystal field multiplet theory, and first-principles calculations, we probe the electronic structure within such polar vortices in [(PbTiO3)16/(SrTiO3)16] superlattices at the atomic scale. The peaks in Ti $$L$$ L -edge spectra shift systematically depending on the position of the Ti4+ cations within the vortices i.e., the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…However, in the first two works only average signals over the domains within the thickness of the TEM specimen could be recorded, and the comparison with first principles required to take the root-meansquare polarization and average tetragonality for each ð001Þ layer of the superlattice. The latest step in this direction (Susarla et al, 2021), where the EELS spectra were recorded with atomic resolution, was recently taken. It was shown how the peaks in Ti L-edge EEL spectra shift systematically depending on the position of the Ti 4þ cations within the vortices, i.e., with the direction and magnitude of the local dipole.…”
Section: Interplay Between Electronic and Atomic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…However, in the first two works only average signals over the domains within the thickness of the TEM specimen could be recorded, and the comparison with first principles required to take the root-meansquare polarization and average tetragonality for each ð001Þ layer of the superlattice. The latest step in this direction (Susarla et al, 2021), where the EELS spectra were recorded with atomic resolution, was recently taken. It was shown how the peaks in Ti L-edge EEL spectra shift systematically depending on the position of the Ti 4þ cations within the vortices, i.e., with the direction and magnitude of the local dipole.…”
Section: Interplay Between Electronic and Atomic Structurementioning
confidence: 99%
“…Note how Ti 4þ can possibly be reduced to Ti 3þ , especially under reducing (or oxygen deficient) conditions. However, this can be readily checked with spectroscopic methods such as EELS (Susarla et al, 2021). Similar PbTiO 3 =SrTiO 3 superlattices grown under slightly different conditions might be prone to display oxygen vacancies and larger concentrations of Ti 3þ close to the vortex core.…”
Section: Interplay Between Electronic and Atomic Structurementioning
confidence: 99%
“…In the perovskite oxides, the existence of O vacancies ( V O ) generally leads to the generation of Ti 3+ , which eventually introduces free carriers into the system and forms a breakdown path under the external electric fields . As shown in Ti L -edge XAS and EELS spectra (Figures a and S21), no trace of Ti 3+ is detected because the existence of Ti 3+ will tend to decrease the intensity of the t 2g peak with the 3d 1 configuration, shift the L 2 and L 3 edges toward a lower energy, or broaden both the t 2g and e g peaks on the low-energy side together . This suggests that the generation of Ti 3+ ions is suppressed by introducing Mn atoms and can be confirmed by Ti 2p XPS characterizations (Figure S22).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that the elastic boundary condition is the key factor that determines the emergence of different topological phases. The vortex phase only exists in the (PTO)/(STO) superlattice on the DyScO 3 substrate, which renders a relatively small compressing strain to the superlattice. , In contrast, polar skyrmions exist in the (PTO)/(STO) superlattice on the STO substrate, where the substrate/superlattice mismatch strain is more compressive. ,,, …”
mentioning
confidence: 99%